Hubungan pola makan dengan sindroma metabolik pada karyawan PT.Unocal oil company di offshore Balikpapan Propinsi Kalimantan Timur - Sri Sudarminingsih; Wiryatun Lestariana; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2007)
Background: Prevalence of metabolic syndrome has significantly increased in both developed and developing countries. Criteria of metabolic syndrome includes: body mass index of > 27, and male waist circumference of > 102 cm which could be followed by fasting blood glucose level of >110 mg/dl. Other symptoms are blood pressure and triglyceride (of > 130/85 mm Hg and > 150 mg/dl respectively) and decrease in high density lipoprotein to < 40 mg/dl.Objective: This research was aimed to explore the extent to which food habit relates with metabolic syndrome among offshore workers employed by Unocal Oil Company Ltd. Located in Balikpapan.Method: The study which was an observational-analytical was then carried out using case-control design, with comparison 1:1 (matched case control). Nutrients intake measured using the 3 x 24 hours recall method. Chi squares, t- test, odd ratios, and logistic regressions were performed to determine statistical significant among variables.Result: The study showed that energy intake > 110% recommended daily allowance (RDA) between case and control group was significantly different (OR= 7.7; 95% CI= 3.1-18.8). This was also true for the case of total carbohydrate > 60%, (OR= 3.98, 95% CI= 1.6-9.8), refined carbohydrate > 5% (OR= 7.4; 95% CI= 2.9-18.7), total protein > 20% (OR= 3.2; 95% CI= 1.2-8.4), and fat > 20% (OR= 5.04; 95% CI= 1.578-16.1). Logistic regressions were performed to determine statistical significant among variables candidate and the result showed it was significant for refined carbohydrate, energy intake and old work in offshore (p<0.05).Conclusion: This study indicate that nutrient intake was higher than of RDA, it was closely related to the incidence of metabolic syndrome: refined carbohydrate, energy intake and old offshore workers employed (p < 0.05).